Formulation and Development Modified Release Apremilast Pellets - Nandgude, Dr. Tanaji D. (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The aim of the present study is to develop and evaluate modified release apremilast pellets for the treatment of rheumatoid arthritis (RA). This disease directly depends on the circadian rhythm of the body, i.e. the maximum joint stiffness generally higher during the morning. The modified release apremilast pellets can be taken before bedtime and capable of releasing drug after a predetermined lag time. Materials and Methods: Apremilast pellets were prepared employing carboxymethyl tamarind kernel powder (CMTKP) as a novel natural excipient using the extrusion-spheronization technique. The apremilast pellets were prepared using blend of microcrystalline cellulose (MCC), lactose, TKP, and crospovidone. The process variables such as spheronizing speed, amount of spheronizing aid (MCC), and binder (TKP) were optimized and reported. Results and Discussion: The obtained pellets were subjected for determination of percentage yield, hardness, physicochemical properties, and particle size analysis. The prepared pellets were further coated with Eudragit L100 release rate retardant polymer, using fluidized bed processor by Wurster technique. Increasing the level of the Eudragit L100 coating retarded the water uptake and thus prolongs the lag time for the release of the drug. The 10% Eudragit L100 coating gave the least release in 0.1 N HCl in 2 h, in next 5 h 97.4% release was observed in phosphate buffer. Conclusion: A significant result obtained with the study indicates that modified release pellets prepared by extrusion-spheronization technique can successfully be further explored and employed in the treatment of RA as well as other diseases characterized by circadian rhythm.